(untitled) (Biodiversitas Journal of Biological Diversity, 2016)
A total of 150 cattle consisting of 3 breeds (Bali, Madura and Ongole) of Indonesian native cattle were used in this study. The aims of the study were to identify and characterize polymorphisms in the growth hormone loci of those breeds of cattle. The genomic DNA was extracted using Wizard genomic DNA purification system from Promega. Two fragments of growth hormone gene were amplified using PCR and continued with RFLP using restriction enzymes of AluI and MspI. Polymorphisms were found at both loci of GH-L1 and GH-L2 of the growth hormone gene by PCRRFLP analysis in all breeds of those cattle. Â© 2002 Jurusan Biologi FMIPA UNS Surakarta Keywords: PCR-RFLP, growth hormone gene, polymorphism, Indonesian local cattle.